In the land of saints and sinners [videorecording (DVD)] - McNally, Mark Michael; Loane, Terry, 1966-; Neeson, Liam; Condon, Kerry, 1983-; Gleeson, Jack; Hinds, Ciarán, 1953-; Greene, Sarah, 1984- (Samuel Goldwyn Films, 2024)
In a remote Irish village, a damaged Finbar is forced to fight for redemption after a lifetime of sins, but what price is he willing to pay? In the land of saints and sinners, some sins can't be buried.